PRACTICE AND WAYS OF COMBATING SHADOW ECONOMIC ACTIVITY - Korol, V.S. (The actual problems of regional economy development, 2017)
Weak governance and entities control causes separation of economic space to the official and shadow segment. Separation of economic area state to the official (socio-positive) and informal (social-negative) segment is based on the quality of economic management on the part of state power and control. The main purpose of the article is to analyze the factors that make up the shadow economy with current state of economic interests of Ukraine regarding national economy legalization. One of major problems of present time in Ukraine is reflected in the article – shadow economy which paralysed almost all spectrum of national economy and is a main barrier for further development of our state. Analysis of tendencies, features and state of this negative phenomenon in the economy of Ukraine are conducted. The special attention is turned on the leading role of the state in overcoming of this problem. Suggestions and methods of protecting are mine-out from further tinization of home economy, and also finding of ways of exit from a crisis.